KARAKTERISTIK PEMIMPIN DALAM ISLAM - L.man, Yovenska (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2019)
Abstact: There are many differences of opinion from political elites, statesmen and even ulemas in Indonesia about the worthiness of a leader and the character of the candidates for the leader themselves which are ideal for this ideological Pancasila country. This pluralistic country with many tribes, cultures and even religions has invited controversies that are quite long and sustainable even often arguing with each other even blaspheming with each other with a variety of hujjah which is brought up as a reference in order to defend the arguments of each group both by the elite politics, culture and even religious leaders. Therefore, the author feels it is important to discuss briefly, clearly but densely contained in this journal, how Islam as the majority religion in the equatorial emerald land responds to endless differences of opinion and can result in divisions between the nation's children and even Muslims themselves.Keywords: Difference of Opinion; Feasibility; Islam.